Analysis of mobile learning philosophy based on ontological, epistemological, and axiological aspects - Darlin Darlin; Moch. Nursalim; Ruqoyyah Fitri; Hermanu Irawan; M. Saleh Laha; Nurlin Nurlin (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2026)
This study aims to analysis the philosophical foundation of Mobile Learning (M-Learning) through ontological, epistemological, and axiological perspectives using the Narrative Literature Review method on 11 indexed scientific articles. The data showed that the focus of the study was dominated by the axiological aspect with the frequency of occurrence of 7 articles (45.5%), followed by the epistemological aspect as many as 6 articles (36.4%), and the ontological aspect as many as 4 articles (18.2%). The results of the ontological analysis show that M-Learning is understood as a flexible, transformative, and ubiquitous learning reality, opening up the possibility of learning across space and time. Epistemologically, the findings confirm that M-Learning reinforces contextual, collaborative, and experiential knowledge constructions, although most implementations are still at the substitution stage and have not yet reached a full epistemic transformation. The axiological aspect appears as the biggest contribution, highlighting the value of inclusivity, equal access, learning motivation, and character formation as the main impact of M-Learning. The discussion shows that the three aspects interact with each other hierarchically, where ontological reality becomes the basis for epistemological processes, while axiological values function to direct and evaluate the ethical application of M-Learning. The conclusion M-Learning has a strong philosophical dimension, particularly in its axiological aspects, which emphasise value, access, and inclusivity, supported by epistemological and ontological aspects that demonstrate active and flexible learning. However, because it is based on only 11 studies, these findings cannot be generalised globally.